The effectiveness of positive psychology interventions in enhancing positive behaviors and family relationships in Hong Kong: A community-based participatory research project*. Issue 1 (2nd January 2016) - Zhou, Qianling; Chan, Sophia Siu-chee; Stewart, Sunita M.; Leung, Charles Sai-cheong; Wan, Alice; Lam, Tai Hing
Abstract : This paper describes a program of brief, universal, positive psychology-based interventions to increase targeted behaviors that enhance family relationships, developed and delivered to over 1500 participants using a community-based participatory approach. The cluster-randomized design combined interventions based on one of three themes (gratitude, hope, or open-mindedness) in one of two structures (intervention, or intervention with planning). The latter structure supplemented with materials and exercises derived from the Health Action Process Approach model of behavior change. Planning was more effective in increasing attitude and intention to perform behaviors, frequency of the targeted behaviors, and family health and happiness (Cohen's d s: 0.10–0.16, p < 0.05), particularly in the theme targeting open-mindedness. Qualitative data supported effectiveness. This project was a first effort to develop a large-scale preventive psychological intervention in an understudied culture with the goal of maximizing acceptability and utilization by involving community stakeholders in every stage of the design.